Log(13)+log(15)=log

Simple and best practice solution for Log(13)+log(15)=log equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(13)+log(15)=log equation:


Simplifying
Log(13) + log(15) = log

Reorder the terms for easier multiplication:
13goL + log(15) = log

Reorder the terms for easier multiplication:
13goL + 15glo = log

Reorder the terms:
15glo + 13goL = log

Solving
15glo + 13goL = glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1glo' to each side of the equation.
15glo + -1glo + 13goL = glo + -1glo

Combine like terms: 15glo + -1glo = 14glo
14glo + 13goL = glo + -1glo

Combine like terms: glo + -1glo = 0
14glo + 13goL = 0

Factor out the Greatest Common Factor (GCF), 'go'.
go(14l + 13L) = 0

Subproblem 1

Set the factor 'go' equal to zero and attempt to solve: Simplifying go = 0 Solving go = 0 Move all terms containing g to the left, all other terms to the right. Simplifying go = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(14l + 13L)' equal to zero and attempt to solve: Simplifying 14l + 13L = 0 Reorder the terms: 13L + 14l = 0 Solving 13L + 14l = 0 Move all terms containing g to the left, all other terms to the right. Add '-13L' to each side of the equation. 13L + -13L + 14l = 0 + -13L Combine like terms: 13L + -13L = 0 0 + 14l = 0 + -13L 14l = 0 + -13L Remove the zero: 14l = -13L Add '-14l' to each side of the equation. 14l + -14l = -13L + -14l Combine like terms: 14l + -14l = 0 0 = -13L + -14l Simplifying 0 = -13L + -14l The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| ln(x+4)=1 | | 6*7-2=x | | 0.75(4x-1)=0.25(6x-1) | | 9-5(n+6)=32 | | 42-m=2m-3 | | D^4+5d^3+6D^2-4D-8=0 | | (D^4+5d^3+6D^2-4D-8)y=0 | | 4cosx^4-cosx^2+1=0 | | 5(4+x)-1=2(x+10)-4x | | 4x=120-2x | | 3x+2x=160 | | 800x=20 | | 21-x=67 | | 97=32+x | | X-41=77 | | (x-17)=24-13 | | 3(2x-2)-4x=8 | | 5x+4=40-8x | | 2x*x=200 | | 7x-9+3x=8x-3 | | -7=9-2z | | 5x-7+2x=6x+1 | | 2+x-5-2x-7=3x+7 | | 3y+7=2y+3 | | 2m(3M)=0 | | 18+7n=-17 | | 3x=-3+30 | | -2(-2x+5)=50+2x | | 2+x-5-2x-7=3x-7 | | (X+4)(3x-12)=0 | | X^2+18=67 | | -i+5+2i+12=12 |

Equations solver categories